2020
DOI: 10.5603/arm.a2020.0138
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking and Drug Abuse with Treatment Failure in Individuals with Tuberculosis: A Case-Control Study

Abstract: Introduction: Treatment failure in tuberculosis (defined as a positive sputum smear 5 months after the initiation of anti-TB treat-ment) is a major threat to the control over TB. This study aimed to investigate the association of smoking and drug abuse with treatment failure among individuals with TB. Material and methods: Out of 286 TB patients with available data registered by the health system of Hamadan Provinces in western Iran, 24 TB patients with treatment failure (positive sputum smear, 5 months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Regarding treatment failure, nine of 12 identified studies provided risk estimates, all reporting increased risk with tobacco use. 26 , 42 , 52 , 57 , 62 , 74 , 82 , 93 , 119 , 123 , 126 , 138 So-called unsuccessful treatment, which combined any outcome other than cure or completion of treatment, was reported in 28 studies. 24 , 49 , 60 , 61 , 65 , 68 , 71 , 73 , 78 , 80 , 85 , 87 , 90 , 91 , 94 , 95 , 104 , 107 , 108 , 114 , 117 , 122 , 123 , 126 , 137 , 140 , 145 , 146 Of these, the risk could not be extracted from four studies, 24 , 49 , 61 , 137 whereas most of the remaining ones reported increased risk, including three studies that included the use of ST products.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding treatment failure, nine of 12 identified studies provided risk estimates, all reporting increased risk with tobacco use. 26 , 42 , 52 , 57 , 62 , 74 , 82 , 93 , 119 , 123 , 126 , 138 So-called unsuccessful treatment, which combined any outcome other than cure or completion of treatment, was reported in 28 studies. 24 , 49 , 60 , 61 , 65 , 68 , 71 , 73 , 78 , 80 , 85 , 87 , 90 , 91 , 94 , 95 , 104 , 107 , 108 , 114 , 117 , 122 , 123 , 126 , 137 , 140 , 145 , 146 Of these, the risk could not be extracted from four studies, 24 , 49 , 61 , 137 whereas most of the remaining ones reported increased risk, including three studies that included the use of ST products.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the increased risk of reinfection among this vulnerable population further complicates their treatment outcomes ( 33 ). Persistent exposure to TB in environments where substance abuse is prevalent can lead to recurring infections, making it challenging to achieve successful treatment outcomes ( 34 ). Moreover, the issue of poor treatment adherence among individuals grappling with addiction plays a critical role in the treatment’s effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, uncontrolled asthma was found to be prevalent in (58 %) of primary care provider sites [14]. Ethiopia has more prevalent poorly controlled asthma ( 71.67 %) [15]. Asthma control was poor in all 11 Middle East and North African countries according to ESMAA study evaluation (41.5%) [16].…”
Section: Introductionmentioning
confidence: 99%